Dual enzyme responsive mannose-6-phosphate based vesicle for controlled lysosomal delivery. Issue 1 (8th December 2020) - Mondal, Basudeb; Dutta, Tahiti; Sen Gupta, Sayam
Abstract : Dual enzyme responsive stable biomimetic vesicles composed of mannose-6-phosphate lipid can encapsulate and deliver dual dye/drug and protein/enzyme exclusively to the lysosome in HEK-293 cells. Abstract : Dual enzyme responsive stable biomimetic vesicles composed of mannose-6-phosphate lipid can encapsulate and deliver dual dye/drug and protein/enzyme exclusively to the lysosome in HEK-293 cells. The release of the cargo from the vesicles can be temporally controlled due to the enzyme responsive morphology change of the M6P lipid assembly.